Tafsir al-Qur’an bi’l Qur’an: The Hermeneutics of Imitation and Adab in Ibn ‘Arabi’s Interpretation of the Qur’an - Zamir, Syed Rizwan (Islamic Studies, 2011)
It is well-established in scholarship that the Qur’an plays a vital role in Ibn ‘Arabi’s writings and spiritual teachings. Ibn ‘Arabi himself is conscious of the centrality of the Qur’an to his works. The hidden analogs between the Qur’an and Ibn ‘Arabi’s writings explain the seemingly abrupt transitions from one topic to another in the chapters of Futuhat or the non-chronological presentation of the wisdom associated with the various prophets in the Futuhat. Although these strong connections between the Qur’an and the Shaykh’s writings have been noted and demonstrated by many, and some of the general hermeneutical principles documented, a more in-depth examination of his concrete exegetical method remains to be done. This short essay carries out this task. It highlights the main features of Ibn ‘Arabi’s hermeneutics, his own prescriptions for the interpretive method, and how it was, or was not, enacted and embodied in his writings.